Peningkatan Pemahaman Konsep Kebisingan dan Emisi Karbon Kendaraan Bermotor di Jalan Lapangan Golf - Nasution, Dinda Azria; Rahmadhani Fitri; Muhammmad Furqan (Arsil Media, 2024)
The purpose of this service activity is to provide an increased understanding of the concept of noise and carbon emissions of motorized vehicles located on Golf Course Road. Traffic noise and carbon emissions are environmental problems that have an impact on public health. The method used is field observation by measuring the number of vehicles, types of vehicles, noise levels using a decibel meter, and estimating carbon emissions using an estimative approach based on the number of vehicles and the average carbon emissions of each type of vehicle. This service shows the importance of periodic monitoring of noise and air pollution as a basis for urban environmental policy making. This activity went well, so that it was able to provide an increase in the number of vehicles.